Pengaruh Penggunaan Larutan Daun Bandotan (Ageratum conyzoides) terhadap Kadar Glukosa Darah Ikan Koi (Cyprinus carpio) Pasca Transportasi [Influence Use Of Bandotan (Ageratum conyzoides) To Rate Koi Fish (Cyprinus carpio) Blood Glucose After Transportation] - Laksmi Sulmartiwi; Sri Harweni; Akhmad Taufiq Mukti; Rr. Juni Triastuti (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Transportation makes stress for fish because of high density and decreasing of water quality. Stress can increase blood glucose. Bandotan have Ca blocking effect. The Ca blocking effect occur in reticulum endoplasmic in smooth muscle. This research aimed to identify bandotan leaf effect in transport medium on blood glucose of koi fish post transportation and to identify best dosage of bandotan leaf on koi fish tranport medium to decrease the blood glucose of koi fish post transportation. Research method used was experimental. Treatment used was providign different bandotan leaf dossage: A (0 g/L), B (0.45 g/L), C (0,9 g/L), D (1.35 g/L) and E (1.8 g/L) and each treatment was repeaetd four times. Main parameter observed in this research was koi fish blood glucose every eight hours for twenty four hours and supporting parameter consisted of: water quality and fish mortality rate. Then the data obtained were prepared using ANOVA, continued by Dunnett Test and then by Duncan's Multiple Distance. Research result shwoed that bandotan leaf supply in transport medium had no effect on koi fish blood glucose post transportation and highest dosage of bandotan leaf in transport medium on blood glucose of koi fish post transportation was 0.45 g/L.